2021
DOI: 10.1186/s12995-020-00290-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and DNA damage in agricultural workers after exposure to pesticides

Abstract: Background Recent epidemiological studies on workers describe that exposure to pesticides can induce oxidative stress by increased production of free radicals that can accumulate in the cell and damage biological macromolecules, for example, RNA, DNA, DNA repair proteins and other proteins and/or modify antioxidant defense mechanisms, as well as detoxification and scavenger enzymes. This study aimed to assess oxidative stress and DNA damage among workers exposed to pesticides. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 46 publications
2
16
0
2
Order By: Relevance
“…Pesticides comprise a vast number of compounds, with different chemical structures, different organisms, and molecular targets as well as biological effects being used for crop and postharvest protection in the agricultural sector [ 1 , 2 ]. The term pesticide includes fungicides, herbicides, insecticides, molluscicides, nematicides, rodenticides, plant growth regulators, and other compounds which are classified according to the target pest [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides comprise a vast number of compounds, with different chemical structures, different organisms, and molecular targets as well as biological effects being used for crop and postharvest protection in the agricultural sector [ 1 , 2 ]. The term pesticide includes fungicides, herbicides, insecticides, molluscicides, nematicides, rodenticides, plant growth regulators, and other compounds which are classified according to the target pest [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with the above, it has been widely demonstrated that pesticide exposure favors ROS production and, with it, oxidative stress conditions [159,182,183]. ROS can modulate the activity of a wide variety of Ca 2+ channels, pumps, and exchangers.…”
Section: Discussionmentioning
confidence: 83%
“…This is biologically plausible as polymorphisms in paraoxonase 1, an enzyme that detoxifies organophosphates,31 have been associated with the development of ALS,32 and high exposure to organophosphates can result in OP-induced delayed neuropathy, a condition akin to ALS 14. Organophosphates also induce oxidative stress,33 which plays an important role in the pathogenesis of MND 34. We observed an elevated MND risk from exposure to pyrethroids insecticides, which is consistent with an earlier case report that presented a patient who developed MND after 3 years of chronic exposure to pyrethroids 35.…”
Section: Discussionmentioning
confidence: 99%